2022
DOI: 10.15586/qas.v14i1.993
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of rice microbial communities under different storage conditions using culture-dependent and -independent techniques

Abstract: Rice is a staple food for over half of the world’s population, and fungal spoilage in stored rice may occur when the moisture content and temperature are conducive. Aspergillus sp. and Penicillium sp. are the most harmful toxigenic species that produce harmful mycotoxins. Molds pose a potential threat to public health and cause a huge economic loss. Therefore, it is of great importance to find out how molds multiply in rice. This study focused on the isolation and identification of fungi presented in rice and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Pantoea, Allorhizobium-Neorhizobium-Parahizobium-Rhizobium, Lactobacillus, and Pseudocitrobacter were the most dominant bacterial genera in the rice grain sample. The main genera detected from the microbial community in this study were consistent with previous studies [48]. The relative abundance of Lactobacillus (20.47%) and Alternaria (26.04%) was highest in the rice grains stored under the condition of normal temperature, horizontal ventilation, and nitrogen gas atmosphere compared with the other two storage conditions (Figure 3E,F).…”
Section: Determination Of Microbial Community Structuresupporting
confidence: 90%
“…Pantoea, Allorhizobium-Neorhizobium-Parahizobium-Rhizobium, Lactobacillus, and Pseudocitrobacter were the most dominant bacterial genera in the rice grain sample. The main genera detected from the microbial community in this study were consistent with previous studies [48]. The relative abundance of Lactobacillus (20.47%) and Alternaria (26.04%) was highest in the rice grains stored under the condition of normal temperature, horizontal ventilation, and nitrogen gas atmosphere compared with the other two storage conditions (Figure 3E,F).…”
Section: Determination Of Microbial Community Structuresupporting
confidence: 90%
“…Another study confirmed that the storage time and granary location had significant effects on the quantity of molds and bacteria population [11]. Similarly, the fungi community of newly stored rice was more diverse than those stored for a long time [12].…”
Section: Introductionmentioning
confidence: 75%
“…Rice ( Oryza sativa ) is a popular staple food and is frequently consumed by the world’s population [ 1 , 2 ]. This commodity is rich in essential nutrients, such as proteins, carbohydrates, and vitamins, and provides two-thirds of caloric requirements [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%